THE IMPORTANCE OF IMPLEMENTING THE TRAFFIC SEPARATION SCHEME (TSS) IN MAINTAINING MARINE ENVIRONMENTAL SAFETY IN THE LOMBOK STRAIT - A, Suryadi (Politeknik Ilmu Pelayaran Semarang, 2024)
Quite a few ships passing along the ALKI II route pollute the sea by dumping dirty water or waste, where this act of pollution often occurs at night. The government regulates a scheme for separating ship traffic in the Lombok Strait using the Traffic Separation Scheme (TSS) system as an effort to improve shipping safety and security as well as protect the maritime environment in Indonesian waters. The aim of this research is to determine the application of the TSS system and the effect of implementing the TSS system in maintaining the safety of the maritime environment in the Lombok Strait. In this research, the method used is comparative descriptive with a quantitative approach. Data collection was carried out by distributing questionnaires and interviews. From the data obtained, analysis was carried out using SPSS software. Based on research results, the implementation of the TSS system aims to facilitate more effective traffic management and prioritize shipping safety and protection of the marine environment. From the results of testing the research hypothesis, there is a partial positive and significant influence. The implementation of the TSS system in the Lombok Strait has helped reduce and manage traffic in the Lombok Strait channel.